2014
DOI: 10.1038/nn.3779
|View full text |Cite
|
Sign up to set email alerts
|

Reward processing by the lateral habenula in normal and depressive behaviors

Abstract: The brain reward circuit has a central role in reinforcing behaviors that are rewarding and preventing behaviors that lead to punishment. Recent work has shown that the lateral habenula is an important part of the reward circuit by providing ‘negative value’ signals to the dopaminergic and serotonergic systems. Studies also suggest that dysfunction of the lateral habenula is associated with psychiatric disorders including major depression. In this review, we first discuss insights gained from neuronal recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
346
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(371 citation statements)
references
References 97 publications
(141 reference statements)
19
346
1
5
Order By: Relevance
“…These phenotypes are not restricted to zebrafish: Lat À/À mice also show alterations in several brain regions including cortex and habenula, a structure that plays a central role in the positive and negative reinforcements of the reward process. [51][52][53] Cd247 À/À mice show brain morphological defects, in particular reduced glutamatergic synaptic activity in the retina 54 and synaptic plasticity in the hippocampus, 41 as well as impaired learning and memory, a T cell-independent mechanism. 44 In zebrafish, ZAP70 is expressed ubiquitously in early development, and highly and specifically in the head from the 16-somite stage, with low expression level throughout the rest of the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypes are not restricted to zebrafish: Lat À/À mice also show alterations in several brain regions including cortex and habenula, a structure that plays a central role in the positive and negative reinforcements of the reward process. [51][52][53] Cd247 À/À mice show brain morphological defects, in particular reduced glutamatergic synaptic activity in the retina 54 and synaptic plasticity in the hippocampus, 41 as well as impaired learning and memory, a T cell-independent mechanism. 44 In zebrafish, ZAP70 is expressed ubiquitously in early development, and highly and specifically in the head from the 16-somite stage, with low expression level throughout the rest of the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…In the habenula, GPR139-positive neurons project axons via the fasciculus retroflexus to the interpeduncular nucleus, where both GPR139 and b-gal immunoreactivity is detected. The expression of GPR139 in the medial habenula is interesting, as the mammalian habenula is involved in regulating the activities of serotonergic and dopaminergic neurons (Hikosaka, 2010;Proulx et al, 2014). In contrast to the lateral habenula, the medial habenula is relatively understudied.…”
Section: Gpr139 Is Activated By L-tryptophan and L-phenylalaninementioning
confidence: 99%
“…Function of these monoaminergic pathways is controlled by inhibitory and excitatory neurons, including important populations residing locally within the monoaminergic nuclei as well as in the adjacent midbrain and anterior hindbrain (Russo and Nestler, 2013;Lammel et al, 2014;Proulx et al, 2014;Morello and Partanen, 2015). Dysfunction of monoaminergic circuits is thought to lead to a multitude of psychiatric and neurophysiological disorders, such as schizophrenia, depression, addiction and Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these GABAergic neurons are referred to as dopaminergic neuron-associated GABAergic (D-GABA) neurons . It has been suggested that the RMTg integrates signals from different parts of the brain, including the lateral habenula (LHb), converting them into inhibitory inputs to both DA and 5-HT networks (Lavezzi and Zahm, 2011;Barrot et al, 2012;Bourdy and Barrot, 2012;Proulx et al, 2014;Sego et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation